CAGE14-1 Cruise Report: CAGE research school in Arctic Marine Geology and Geophysics - Bünz, Stefan; Panieri, Giuliana (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
Cruise CAGE 14-1 is one of several cruises in 2014 that will be carried out to collect cross-disciplinary data for addressing the objectives of the Norwegian Centre for Arctic Gas Hydrate, Environment and Climate, CAGE. The Norwegian Research Council funds CAGE for a period of 10 years to addressee main scientific questions about gas hydrate environments in Arctic regions. Cruise CAGE 14-1 was also hosting this year’s AMGG research school cruise with 14 PhD students participating, most of them from CAGE. The cruise focused on acquisition of seismic, oceanographic, atmospheric, geochemical and sediment and benthic fauna sampling data from three target areas: the shallow shelf and shelf edge methane seepage sites at Prins Karls Forelanda sediment drift on the western flank of the Knipovich Ridgethe Vestnesa Ridge Research objectives were planned long the goals of CAGE and its individual work packages, and the teaching would be organized along these goals. Scientific problems that are to be addressed in these two key target areas include the periodicity of seepage (i.e. time scales of active, inactive and reactivated systems), quantification of methane concentrations in surface sediments, water column and above the sea surface, gas and hydrates, the nature of gas sources, and the benthic communities occurring at the seep sites. Specific objectives of cruise CAGE 14-1 were as follows: Hydro-acoustic mapping of methane bubble plumes above shallow and deep-water vent fields.Seismic surveying and multibeam mapping across the contours of the Svyatogor Rise.Sediment sampling using gravity, box and multi-corer for sediment and pore-water geochemical analysesSampling of benthic fauna at several seep sites and reference stations in all three target areas.Acquisition of oceanographic data for measuring oceanographic conditions and methane concentrations in the water column, particularly at the shallow shelf sites. The cruise may be known as: CAGE14_1